Класифікація легкових автомобілів як вид сегментації ринку за продуктом - Кищун, В. (Видавництво Національного університету "Львівська політехніка", 2000)
У статті на основі споживчих якостей легкові автомобілі поділені на чотири типи (дорожні, позадорожники, мінівени і спортивні), а типи, своєю чергою, – на класи. В основу класифікації дорожніх легкових автомобілів покладена їх габаритна довжина. Визначені дев’ять класів (мікро, міні, особливо малий, нижній середній та інші), які охоплюють діапазон довжин від 2,5 до 5,2 і більше матрів. Запропонована універсальна класифікація може використовуватись як спеціалістами з маркетингу, так і виробниками автомобілів. Cousumers and produce are nof the only units of market segmentation. A motorcar is a commodity with such qualitses that harmonize with the main factors of market segmentation according to the cousumers needs. According to the consumption qualities of motor-cars the latter can be divided into the following four types: road motor, offroad motor-cars, minivans and sports motor-cars . These tupes in thei turn can be subdivided into claises. The leugth of a motor-car is laid down the foundation of the roadway motor-car classification. The following nine tupes of motor-cars have been determined frow this point of view (microcars, minicars, especially small cars, small cars, sub-middle cars, ete). These types embrace cars ranging in length from 2.5 m to 5.2 m and more. Theproposed universal classification provides ist adoption both by specialists in marketing and by car manufacturers.